A CREATIVE POWER OF CHARLOTTE BRONTE IN THE VICTORIAN ERA. - Darvishova Gulchehra Kenjabayevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Victorian literature became very important and powerful because it relies on a realistic mode of representation. This article outlines creative power of prominent and popular author of Victorian age Charlotte Bronte.